Preschool developmental concerns and adjustment in the early school years: Evidence from a Scottish birth cohort. (12th August 2019) - Sim, Fiona; Thompson, Lucy; Marryat, Louise; Law, James; Wilson, Philip
Abstract: Background: Preschool language and behavioural difficulties impact on multiple domains of the child's early life and can endure into adulthood, predicting poor educational, social, and health outcomes. Highlighting risk factors associated with poor outcomes following language and behavioural difficulties raised in early childhood may facilitate early identification and intervention. Methods: Data from the Growing Up in Scotland national birth cohort study were used. Language and behavioural difficulties were assessed at age 4 years using parent‐reported language concerns and the Strengths and Difficulties Questionnaire. Measures of adjustment were collated into four key outcome domains: attitude to school life, language and general development, behaviour, and general health at age 6 years. Both univariate and multivariate logistic regression models were fitted in order to explore independent associations between language and behavioural difficulties at age 4 years and adjustment to life circumstances at age 6 years, whilst controlling for other risk factors. Results: Language difficulties at age 4 years increased the odds of the child experiencing difficulty with language and general development, poorer health outcomes, and behavioural difficulties at age 6 years. Behavioural difficulties alone at age 4 years were associated with increased odds of the child experiencing all of the aforementioned outcomes and difficulties in early school life. Lone parent family, low income, and male gender were identified as risk factors for poorer outcomes in the domains measured. At age 4 years, there was no additive effect found with the presence of behaviour difficulties on the relationship between language difficulties and language and developmental outcomes at 6 years. Conclusions: This paper demonstrates language and behavioural difficulties are associated with poor social, educational, health, and behavioural outcomes. Taking seriously parent‐reported concerns and identifying risk factors could limit negative outcomes for the child, their family, and society.